The Effect Of The Application Of Government Accounting Standards On Employee Performance In The Management Agency Finance And Revenue Binjai City - Satria Yuda Atmaja; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
This type of research is a causal associative quantitative research with the aim of analyzing the relationship between variables and determining the influence between two independent (exogenous) variables on bound variables. This research was carried out at the Office of the Financial and Revenue Management Agency of Binjai City, with a population of 186 employees. The sampling technique used is saturated sampling, where all members of the population are sampled. The data used was obtained through a questionnaire distributed to respondents consisting of all employees in various divisions. The results of the study show that the implementation of Government Accounting Standards has a positive and significant effect on Employee Performance. This is evidenced by a t-count value of 39.559, which is greater than the t-table of 1.65309, and a significance value of 0.000, which is smaller than 0.05. A regression coefficient of 0.900 indicates that every 1 point increase in the Implementation of Government Accounting Standards will lead to an increase in Employee Performance by 0.900 points, assuming other variables remain constant. In addition, the results of the determination coefficient test showed an Adjusted R Square value of 0.837 or 83.70%, which showed that the Implementation of Government Accounting Standards had a very high influence on Employee Performance, with the remaining 16.30% influenced by other factors that had not been studied in this study.